Effect of L-Alanine on the Optical Properties of Zinc (Tris) Thiourea Sulfate (ZTS) Single Crystal - , Prasanta Ghosh and Mahendra D. Shirsat*, N.R. Dhumane, S.S. Hussaini, Kunal Datta (Recent Research in Science and Technology, 2010)
The growth of L-Alanine doped Zinc (tris) Thiourea Sulfate single crystal from aqueous solution by low temperature solution growth has been reported in the present investigation. The 1, 2 and 3mole% L-Alanine was doped in saturated ZTS solution. The effect of L-Alanine on SHG property was studied by Kurtz and Perry powder SHG test. The higher enhancement in SHG efficiency was observed at 1mole% L-Alanine doped ZTS. Hence, the growth 1mole% L-Alanine doped ZTS was carried. The grown crystal was characterized by single crystal X-ray analysis, FT-IR, UV-visible spectroscopy and thermal study by TGA and DSC analysis.